2017
DOI: 10.18517/ijaseit.7.1.1479
|View full text |Cite
|
Sign up to set email alerts
|

Object Feature Extraction of Songket Image Using Chain Code Algorithm

Abstract: The study was aimed at determining the feature of a motif found in a Songket image in order to make the object detectable and readable. The method used was image color segmentation in the form of a process of segmentation of the image area based on the similarity in colors, which was continued with the binary process that aims to change the image into binary form (0 and 1), so that it only has two colors namely black and white. This study also used mathematical morphology in detecting objects, by using dilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
11
0
2
Order By: Relevance
“…Feature extraction aims to compute the specific representation of the data that can highlight relevant information [1]. Besides, it is a useful tool for removing irrelevant or redundant information and reducing feature dimensionality [16]. LBP variants are methods under the group of binary descriptors for extracting image features by describing the spatial structure of the gray image texture.…”
Section: Methodsmentioning
confidence: 99%
“…Feature extraction aims to compute the specific representation of the data that can highlight relevant information [1]. Besides, it is a useful tool for removing irrelevant or redundant information and reducing feature dimensionality [16]. LBP variants are methods under the group of binary descriptors for extracting image features by describing the spatial structure of the gray image texture.…”
Section: Methodsmentioning
confidence: 99%
“…The waste of Silungkang tenun songket dye [1,2], West Sumatra as Direct Yellow-27 is a non-biodegradle compound that consists azo. That carcinogenic subtance could cause distrubtion in human body such as harmfull of kidney, cancer [3][4][5], and tumor [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the process carried out showed that the development chain code algorithm can generate the number of objects, the length of chain code, and probable value of rate of appearances of each chain code in a motif, despite there are some objects in a motif. Then the values are stored into the database as The Feature of Songket Motifs [19].…”
Section: Introductionmentioning
confidence: 99%